Thyroid carcinoma Surgical treatment: 37 observations - Suiffet, Walter (Cirugía del Uruguay, 1974)
Our case material for thyroid carcinoma consists of 57 patients and the majority of these tumors ( 83.8 % ) were differenciated. Most frequent clinical appearence consisted of non functioning nodular goiter. Surgery was determined by diagnosis and type of lesion: partial thyroidectomy 81 % total thyroidectomy 2.7 % and incomplete resection of tumor 8.1 %. Dissection of ganglia was performed only_ in cases of clinically colcnized adenopathies. All patients with non differenciated carcinomas died. In differenciated cases there was an overall deathrate of 13 % .